The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3400/avd.oa.18-00075
|View full text |Cite
|
Sign up to set email alerts
|

Original Homebuilt Off-the-Job Training System for Vascular Surgeons: System Analysis and Assessment

Abstract: Objective: We assessed the effectiveness and appropriateness of our original off-the-job training (Off JT) system using data acquired from recruited medical students and doctors.Materials and Methods: We presented our original homebuilt Off JT system, which is simple and inexpensive. In our unique system, we performed anastomosis at the bottom of a plastic pot, which mimics the actual open surgical procedure at a deep site. There were four evaluation points: (A) operating time, (B) performance of anastomosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Anastomosis of grafts or blood vessels is one of the most basic and familiar procedures for vascular and cardiovascular surgeons; therefore, to assess the effectiveness of our suture training, we focused on the thread arrangement in anastomoses. We had previously determined that bite, pitch, and skewness were associated with suturing symmetry and confirmed that bite, pitch, procedural time, and OPRS were strongly correlated [8].…”
Section: Introductionmentioning
confidence: 65%
“…Anastomosis of grafts or blood vessels is one of the most basic and familiar procedures for vascular and cardiovascular surgeons; therefore, to assess the effectiveness of our suture training, we focused on the thread arrangement in anastomoses. We had previously determined that bite, pitch, and skewness were associated with suturing symmetry and confirmed that bite, pitch, procedural time, and OPRS were strongly correlated [8].…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, we studied anastomotic performance under the system and revealed that procedure time, objective score for the skills, and anastomotic quality were considerably correlated. 10) The system was practically used in the Distal Bypass Workshop (http://www.jsvs.org/ja/event/distal_bypass_ workshop/) carried out by the Japanese Society for Vascular Surgery from 2017 to 2019. Our purpose for developing this application of segmentation was derived from the responses to questionnaires administered in the past workshops.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluating suture performance (balance of the suture), we used two factors adopted in our previous study: the bite (the length of a stitch across the graft/tube) and pitch (the interval between stitches). 10) The balance was evaluated with the coefficient of variation (CV) as shown previously. 10) In addition, we adopted another factor-skewness-to evaluate the balance of the angle among stitches, especially in curved suture lines of side-to-end anastomoses.…”
Section: Score Of Suturesmentioning
confidence: 99%
See 2 more Smart Citations